LOCAL USE OF THE "PULSAR" DEVICE IN THE TREATMENT OF PURULENT-NECROTIC COMPLICATIONS OF DIABETIC FOOT SYNDROME - K.U., Sherkulov; A.U, Bobokulov; M.K., Usmonkulov; F.U., Babakulova (Journal of Medical Genetics and Clinical Biology, 2024)
Wounds and wound infections are among the oldest branches of medicine, however, even today, wound treatment remains one of the main problems of surgery. Despite the many methods used and methods of treating wounds, none of them completely satisfies surgeons.